A comparative study of microcystin-LR degradation by electrogenerated oxidants at BDD and MMO anodes. (December 2016) - Zhou, Shiqing; Bu, Lingjun; Yu, Yanghai; Zou, Xu; Zhang, Yansen
Abstract: This study investigated the electrochemical degradation of microcystin-LR (MC-LR) using boron-doped diamond (BDD) anode and mixed metal oxides (MMO, IrO2 Ta2 O5 /Ti) anode in different medium. In-situ electrogenerated oxidants including hydroxyl radical, active chlorine, and persulfate were confirmed in phosphate, chloride, and sulfate medium, respectively. Different from MMO anode, hydroxyl radical was observed to play a significant role in chlorine generation at BDD anode in chloride medium. Besides, BDD anode could activate sulfate electrochemically due to its high oxygen evolution potential, and MC-LR degradation rate increased with the decrease of solution pH. The effects of natural organic matters (NOM) and algal organic matters (AOM) on MC-LR degradation were evaluated and NOM presented stronger inhibition ability than AOM. Furthermore, the intermediates generated in MC-LR degradation in chloride and sulfate medium were identified by LC/MS/MS and possible degradation pathways were proposed based on the experiments results. Benzene ring and conjugated diene bonds of Adda group and double bonds of Mhda group were found to be the reactive sites of MC-LR. Overall, this study broadens the knowledge of electrochemical oxidation in removing microcystins in algae-laden water. Graphical abstract: Highlights: Electrogenerated oxidants were responsible for MC-LR degradation. BDD anode showed better performance in all medium in this study. Possible pathways of MC-LR degradation were proposed.